Encyclopedia of creativity - Runco, Mark A.; Pritzker, Steven R. (San Diego, Calif. : Academic Press, 1999)
The Encyclopedia of Creativity is a set of two volumes viz: vol 1, A-H and vol. 2, I-Z. The encyclopaedia of Creativity is a source book for individuals seeking specialized information about creativity,creative process and motivation. The first vol of the Encyclopedia of Creativity served to establish the study of creativity is a field in itself covering A-H while, vol 2 covered I-H.
Includes bibliographical references and indexes.
kjo 24/10/2018
Ref
Keywords: Creative ability; Creation (Literary, artistic, etc.); Creative ability--Psychological aspects